Reorienting Mining Policy In Indonesia From a Qur’anic and Maqāṣid Al-Sharī‘Ah Perspective Toward Social Justice and Ecological Sustainability - Imdad, Muhamad Khabib; Azkiya, Ahmad Aqiel (Tashwirul Afkar, 2026)
This article re-examines mining practices and policies in Indonesia through the lens of maqāṣid-based Qur’anic exegesis. Mining, as a strategic sector in national economic development, occupies a paradoxical position: on the one hand, it provides significant economic benefits for the state, but on the other, it generates potential harms such as ecological degradation, agrarian conflicts, and social injustice. Public debates, including those raised by Ulil Abshar Abdalla regarding the Islamic legal status of mining, demonstrate that the issue extends beyond economic and political concerns to religious-ethical dimensions. This study employs a qualitative approach using literature review, drawing on classical and contemporary tafsir, Islamic environmental jurisprudence, and mining policy documents. The findings reveal that, within the framework of maqāṣid al-sharī‘ah, mining is essentially mubāḥ (permissible) in itself, but may shift to harām li ghairihi (prohibited due to external causes) when it causes ecological damage and social inequality. The principles of lā ḍarar wa lā ḍirār and taṣarruf al-imām manūṭun bi al-maṣlaḥah emphasize that the state is religiously and ethically obliged to manage mining for the sake of public welfare, environmental sustainability, and social justice. Thus, maqāṣidi exegesis functions not only as a theological framework but also as an ethical-critical instrument to evaluate public policies and to propose more just and sustainable mining governance.